“Ayudar a aquellos artistas que transformaron la canción en un arma de lucha”: O papel das juventudes comunistas na difusão da nova canção Chilena (1968-1973) - Schmiedecke, Natália Ayo [UNESP] (Universidade do Estado de Santa Catarina, 2017)
In a time marked by revolutionary expectation, many young supporters of socialism chose art as a privileged trench in the struggle for a new society. In the musical field, the 1960s saw the emergence of the committed popular musician in Latin America, who began to use his work to take up a position facing contemporary political, social and economic issues. In Chile, the committed song found support in the Communist Party, which was the main responsible for the production and circulation of the repertoire linked to the Chilean New Song until the 1980s. Focusing on the period prior to the military coup of 1973, this article addresses the Party’s cultural policies aimed at the movement, in order to make explicit their role in building national and international networks. Considered an example of revolutionary commitment, the New Song occupied a central place in the catalog of DICAP record label, as well as in ONAE programming and in the pages of Ramona magazine – vehicles run by the Communist Youth of Chile. With this, the Party participated in the very process of definition of the Chilean committed song and became directly associated with this repertoire. Understanding how this relationship occurred, instead of naturalizing it, was the primary objective of the performed study.
The role of the communist youth in the diffusion of Chilean new song (1968-1973)
Keywords: Chilean new song; Communist party of Chile; DICAP; Ramona